1 year seismological experiment at Strokkur in 2017/18 - Eibl, E.P.S.; Walter, T.; Jousset, P.; Dahm, T.; Allahbakhshi, M.; Müller, D.; Hersir, G. P. (GFZ Data Services, 2020)
Abstract Strokkur_1yr is a one year seismological experiment realized at the most active geyser on Iceland by Eva Eibl (University of Potsdam) in collaboration with Thomas R. Walter, Phillippe Jousset, Torsten Dahm, Masoud Allahbakhshi, Daniel Müller from GFZ Potsdam and Gylfi P. Hersir from ISOR Iceland. The geyser is part of the Haukadalur geothermal area in south Iceland, which contains numerous geothermal anomalies, hot springs, and basins (Walter et al., 2018). Strokkur is a pool geyser and has a silica sinter edifice with a water basin on top, which is about 12 m in diameter with a central tube of more than 20 m depth. The aim of the seismic experiment is to monitor eruptions of Strokkur geyser from June 2017 to June 2018 using four broadband seismic stations (Nanometrics Trillium Compact Posthole 20 s). Sensors were buried 30–40 cm deep in the ground at distances of 38.8 m (G4, SE), 47.3 m (G3, SW), 42.5 m (G2, N), and 95.5 m (G1, NE) from Strokkur center. Data gaps represent 15–44 % of the records as during the winter period maintenance intervals were longer and battery drainage was high. However, at any given time, at least one station recorded the eruptions. From this dataset, converted to MSEED using Pyrocko, a catalogue of 70,000 eruptions was determined and further investigated in Eibl et al. (2020) Waveform data are available from the GEOFON data centre, under network code 7L.